Children Handling Procedure in Islamic Criminal Offense in Aceh - Analiansyah, Analiansyah; Abubakar, Ali (Universitas Islam Negeri Jakarta, 2021)
The Law of the Republic of Indonesia authorizes Aceh to implement shari’a law in various sectors, including jināyāt (Islamic criminal law). This additional authority is different from the authority of the Religious Courts (Pengadilan Agama) in other provinces in Indonesia. This article analyzes the process of handling children in criminal cases in the Aceh’s Shari’a Courts in Aceh using the lex specialis derogate legi generalis and the systematic lex specialis principles. The data in this study comes from legal documents and interviews with Shari’a Court judges. The results show that the handling of Islamic criminal offenses involving children has been carried out by referring to existing laws and regulations according to the principle of specificity. However, some issues arise related to human resources and appropriate facilities. Most of the judges have not obtained special training in handling children’s cases, which influenced their knowledge on the issue. Moreover, children involving in legal cases are still treated using similar facilities as adults. These weaknesses, however, can be appropriately resolved by the Shari’a Courts and the Aceh Government. Abstrak:Undang-Undang Republik Indonesia memberikan kewenangan kepada Aceh untuk menerapkan syariat Islam di berbagai bidang, termasuk jināyāt (hukum pidana Islam). Pemerintah Aceh mengeluarkan qanun (Peraturan Daerah) yang mencakup beberapa jarīmah (perbuatan pidana) dan pelaksanaannya menjadi kewenangan Pengadilan Syariah (Mahkamah Syar’iyyah) di Aceh. Kewenangan tambahan ini berbeda dengan kewenangan Peradilan Agama di provinsi lain di Indonesia. Hakim-hakim di pengadilan-pengadilan tersebut tidak mendapatkan pendidikan khusus dalam hukum pidana, terutama kasus-kasus yang melibatkan anak-anak yang telah diatur dalam undang-undang khusus. Kewenangan tambahan dalam memeriksa dan mengadili perkara pidana di Mahkamah Syariah menimbulkan persoalan Sumber Daya Manusia (SDM) baru. Artikel ini menganalisis proses penanganan anak di Pengadilan Syariah di Aceh dengan menggunakan prinsip lex specialis derogate legi generalis dan systematic lex specialis. Hasil penelitian menunjukkan bahwa penanganan tindak pidana Islam yang melibatkan anak telah dilakukan dengan mengacu pada peraturan perundang-undangan yang ada sesuai dengan asas kekhususan. Beberapa kelemahan sumber daya manusia dan infrastruktur dapat diselesaikan dengan baik oleh Pengadilan Syariah dan Pemerintah Aceh.